Development of a human milk protein concentrate from donor milk: Impact of the pasteurization method on static in vitro digestion in a preterm newborn model. (February 2023) - Sergius-Ronot, Mélanie; Suwal, Shyam; Pitino, Michael A.; Shama, Sara; Unger, Sharon; O'Connor, Deborah L.; Pouliot, Yves; Doyen, Alain
Graphical abstract: Highlights: Digestion was similar between raw and pressurized human milk protein concentrate. Human milk protein concentrate digestion is affected by pasteurization. Holder pasteurization had the major impact on amino acids release. Abstract: The impact of high temperature short time (HTST, 72 °C, 15 s), Holder pasteurization- (63 °C, 30 min) and high hydrostatic pressure (HHP, 600 MPa-10 min) was evaluated on the digestibility of human milk protein concentrate (HMPC) by using a static in vitro gastrointestinal digestion system. The results showed that the processing steps used to produce the HMPC induced a decrease in readily available nitrogen (non-protein nitrogen and peptides). Overall, digestibility was similar between pasteurized and raw HMPC (degree of hydrolysis ranged from 26 to 34 %). Lactoferrin was more susceptible to gastric and intestinal digestion after thermal pasteurization . Additionally, the resistance of β-casein to digestion increased after HHP and Holder pasteurization due to aggregation and changes in protein structure. During intestinal digestion, Holder pasteurization induced a higher release of arginine, phenylalanine and tyrosine from HMPC compared to raw and HHP-treated HMPC. Overall, protein structural changes induced by human milk (HM) processing (freeze–thawing and filtration) and pasteurization treatments affected HMPC proteolysis during in vitro digestion. However, protein digestion behaviors were quite similar for raw and HHP-treated HMPC compared to the thermal-treated HMPC, with no effect on lactoferrin digestion. Consequently, pasteurization of HMPC by HHP represents an interesting non-thermal process that preserves the HM bioactive proteins during digestion.